2021
DOI: 10.3389/fmed.2021.649177
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Detection of Double ROS1 Translocations, SDC4-ROS1 and ROS1-GK, in a Lung Adenocarcinoma Patient and Response to Crizotinib

Abstract: ROS1 rearrangement, identified in ~2% of non-small cell lung cancer (NSCLC), has defined a distinctive molecular subtype. Patients with ROS1 fusion have been shown to be highly sensitive to treatment with crizotinib. However, the efficacy of crizotinib in NSCLC patients with double ROS1 fusions remains to be elucidated. Here, we report a 40-year-old male diagnosed with stage IIIA lung adenocarcinoma. Two ROS1 fusions [SDC4-ROS1 (EX2:EX32) and ROS1-GK (EX31:EX13)] were detected simultaneously in tumor tissue of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Using NGS, Xu et al found two ROS1 fusions [SDC4-ROS1 (EX2:EX32) and ROS1-GK (EX31: EX13)] in a patient with lung adenocarcinoma. These results indicated that the patient might be sensitive to ROS1 inhibitors (Xu et al, 2021). Patients harboring ROS1 fusions may benefit from crizotinib if their tumors are metastatic (Cai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Using NGS, Xu et al found two ROS1 fusions [SDC4-ROS1 (EX2:EX32) and ROS1-GK (EX31: EX13)] in a patient with lung adenocarcinoma. These results indicated that the patient might be sensitive to ROS1 inhibitors (Xu et al, 2021). Patients harboring ROS1 fusions may benefit from crizotinib if their tumors are metastatic (Cai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…identified a patient with NSCLC with non-reciprocal/reciprocal ROS1 rearrangement ( ROS1-FBXL17 fusion co-existing with CD74-ROS1 fusion), who obtained an excellent response to crizotinib, and the progression-free survival (PFS) was up to 17 months ( 10 ). However, in another study, a patient with lung adenocarcinoma harboring complex ROS1 fusions ( GK-ROS1 and SDC4-ROS1 ) showed resistance only 8 months after crizotinib therapy ( 7 ). These inconsistent findings suggest that further investigations are needed to explore the efficacy of ROS1 inhibitors in dual ROS1 fusion.…”
Section: Case Presentationmentioning
confidence: 99%
“…To choose the appropriate therapeutic approaches, it is crucial to recognize druggable ROS1 fusions. Previous research rarely reported single reciprocal ROS1 fusions, which kept ROS1 as the 5′ fusion gene without their counterpart of the 3′ ROS1 fusion variant ( 7 ). Although it occurs very rarely, research on this uncommon ROS1 fusion is vital to broaden the genetic landscape of usable ROS1 fusions and to provide personalized precision medicine.…”
Section: Introductionmentioning
confidence: 99%